Agama di Ruang Publik Politik - Muhammad Dawam Rahardjo (Reformed Center for Religion and Society, 2015)
ABSTRACT: The question of the role of religion in the public sphere of politics is because of its history, the three monotheist religions, which is also called the Abrahamic religions. Judaism, Christianity and Islam, and even Hinduism and Buddhism, in maintaining their existences and developments, always get into and even form their own power in a country. Indonesia is a secular nation state, which is not based on any particular religion as a political ideology, and yet its people are multi-religious. Even though the country is not based on religion, but religion has become a source of inspiration in its constitution, namely UUD (Undang Undang Dasar) 1945. On the one hand, people and the state are in unity for mutual support or mutual need. The state cannot be formed without people as its base. On the other hand, people need the state to protect the society. Constitution is needed to control the state and its leader. On the one hand this constitution curbs the power of its leader; and on the other hand it guarantees the fulfillment and the protection of civil rights that stem from human rights. The triangle of these institutions is a reality in the current modern world, especially in Indonesia, where religion has an important role, even though in Europe the stand and the role of religion is in the declining stage due to secularization and secularism principle. Yet the relationship of these three institutions in the current modern context cause a complex issues related to the boundaries of these three institutions. What are the principles that can continuously connects these three so that justice as the main principle can be uphold between the triangle of society, state and religion?KEY WORDS: religion, public sphere, nation, civil rights, human rights